2021
DOI: 10.1007/s00417-021-05285-y
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular fluid biomarkers (liquid biopsy) in human diabetic retinopathy

Abstract: Purpose This article aims to review the impact of detecting and quantifying intraocular biomarkers (liquid biopsy) in both aqueous and vitreous humor in eyes of people affected by diabetes mellitus. Methods This is a detailed review about aqueous and/or vitreous humor sampling in human diabetic eyes for proteomic and/or metabolomic analysis contributing to the understanding of the pathophysiology and treatment effects of diabetic retinopathy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 122 publications
(174 reference statements)
0
27
0
Order By: Relevance
“…To date, a number of new technologies have been employed to study DR, including metabolomics. For instance, metabolic signatures (biomarkers) of DR discovered by metabolomics have been described in several reviews [67][68][69][70]. In this subsection, we summarize and discuss the application of metabolomics to DR.…”
Section: Diabetic Retinopathy (Dr)mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, a number of new technologies have been employed to study DR, including metabolomics. For instance, metabolic signatures (biomarkers) of DR discovered by metabolomics have been described in several reviews [67][68][69][70]. In this subsection, we summarize and discuss the application of metabolomics to DR.…”
Section: Diabetic Retinopathy (Dr)mentioning
confidence: 99%
“…However, in this study, glutamine and glutamic acid were not identified as differential metabolites. With respect to vitreous humor, Midena et al [67] performed a detailed review of aqueous and/or vitreous humor sampling in human eyes from DR patients for proteomic and/or metabolomic analysis. The exact quantification of aqueous and vitreous humor biomarkers can provide valuable insights to retinal diseases and can contribute to precision medicine in ophthalmology.…”
Section: Diabetic Retinopathy (Dr)mentioning
confidence: 99%
“…Cytokines can be harvested from serum, tears, aqueous humor (AH) or vitreous humor (VH) [ 4 , 5 ]. It has been shown that concentrations from AH and VH are comparable [ 6 , 7 ], while the serum quantifications might not directly reflect the intraocular changes. For these findings, ocular immune privilege and blood–ocular barrier were incriminated [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, most OCT devices have a limited imaging range, with the macula and optic disc being the main imaging positions, so peripheral changes may be missed, especially in the early stage of diseases [1,2] . In addition, the detailed disease phenotypes may fail to be detected and distinguished by current sophisticated imaging techniques [3,4] . With the development of precision medicine, including the use of objective quantitative indices and omics methods, an important opportunity has been offered to understand the pathological characteristics and the diagnosis/treatment of ME.…”
Section: Introductionmentioning
confidence: 99%